2018
DOI: 10.1016/j.appet.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral processing on appetite and food intake – A systematic review and meta-analysis

Abstract: Food delivers energy, nutrients and a pleasurable experience. Slow eating and prolonged oro-sensory exposure to food during consumption can enhance the processes that promote satiation. This systematic review and meta-analysis investigated the effects of oral processing on subjective measures of appetite (hunger, desire to eat) and objectively measured food intake. The aim was to investigate the influence of oral processing characteristics, specifically "chewing" and "lubrication", on "appetite" and "food inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
66
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 70 publications
1
66
2
2
Order By: Relevance
“…It was hypothesized that more chewing would lead to lower food intake, as reported in previous studies. 3 Interestingly, results found that snack intake was only lowered after the consumption of the soft/high lubricating preload sample (1.5κC0.5NaA) compared to the hard/low lubricating preload (3κC), but not after the control, suggesting that not the chewing but the lubricating properties governed subsequent intake of a salty snack. Sensory ratings for the different preloads did not reveal a significant difference in terms of pleasantness, strength of mint flavour or sweetness, and therefore these characteristics could not account for the suppressed food intake after the soft/high lubricating preload (1.5κC0.5NaA).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…It was hypothesized that more chewing would lead to lower food intake, as reported in previous studies. 3 Interestingly, results found that snack intake was only lowered after the consumption of the soft/high lubricating preload sample (1.5κC0.5NaA) compared to the hard/low lubricating preload (3κC), but not after the control, suggesting that not the chewing but the lubricating properties governed subsequent intake of a salty snack. Sensory ratings for the different preloads did not reveal a significant difference in terms of pleasantness, strength of mint flavour or sweetness, and therefore these characteristics could not account for the suppressed food intake after the soft/high lubricating preload (1.5κC0.5NaA).…”
Section: Discussionmentioning
confidence: 95%
“…This is inconsistent with previous research, which showed that higher level of chewing did indeed reduce food intake. 3,14,18 This might be explained by the short exposure time of 10 minutes and the low amount of elicited chewing in this period, indicating that the total chewing time may not have been sufficiently long enough to influence food intake. Future research incorporating more hydrogel pieces into the preload to increase overall chewing time may find a more pronounced effect on food intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations